2006
DOI: 10.1242/dev.02521
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regulation of shoot development inArabidopsis thalianabymiR156and its targetSPL3

Abstract: SPL3, SPL4 and SPL5 (SPL3/4/5) are closely related members of the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE family of transcription factors in Arabidopsis, and have a target site for the microRNA miR156 in their 3Ј UTR. The phenotype of Arabidopsis plants constitutively expressing miR156-sensitive and miR156-insensitive forms of SPL3/4/5 revealed that all three genes promote vegetative phase change and flowering, and are strongly repressed by miR156. Constitutive expression of miR156a prolonged the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
1,115
4
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 986 publications
(1,182 citation statements)
references
References 60 publications
57
1,115
4
6
Order By: Relevance
“…The sequential action of Group I miRNAs, miR156/157 and miR172 control vegetative traits and the transitional timing from vegetative to reproductive phase during development 29 . Manipulations of the expression in these miRNAs can change Arabidopsis flowering time; for example, the overexpression of miR156 prolongs the juvenile phase and delays flowering time 29,34,41 , while its reduction is similar to SPLs overexpression, leading to the early-flowering phenotype 29,42 . Overexpressed miR172 also results in the early-flowering phenotype 29,43 .…”
Section: Discussionmentioning
confidence: 99%
“…The sequential action of Group I miRNAs, miR156/157 and miR172 control vegetative traits and the transitional timing from vegetative to reproductive phase during development 29 . Manipulations of the expression in these miRNAs can change Arabidopsis flowering time; for example, the overexpression of miR156 prolongs the juvenile phase and delays flowering time 29,34,41 , while its reduction is similar to SPLs overexpression, leading to the early-flowering phenotype 29,42 . Overexpressed miR172 also results in the early-flowering phenotype 29,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the phenotype was milder than that of the miR156 overexpressers, in which expression of eight additional SPL genes is strongly reduced (Schwab et al, 2005), this finding indicated an important redundant effect of SPL9 and SPL15 on plastochron length. Based on overexpression experiments, the SPL3 gene has been implicated primarily in the regulation of flowering time and phase change (Cardon et al, 1997;Wu and Poethig, 2006). Unfortunately, knockout alleles for the other two small SPL genes, SPL4 and SPL5, are not available, making it more difficult to test whether redundancy among the three small SPL genes masks their contribution to plastochron length.…”
Section: Role Of Mir156-targeted Spl Genes In Determining Plastochronmentioning
confidence: 99%
“…CUC2 protein is thought to act in the development of embryos and flowers (Aida et al, 1997). The second, SPL5, is part of the SPL family and has overlapping functions Genetic control of flowering and maturity dates in Prunus E Dirlewanger et al with SPL3 and SPL4 in the regulation of vegetative phase change in Arabidopsis (Wu and Poethig, 2006). The third one, SPA3, is a member of the SPA family that is essential for the inhibition of flowering under non-inductive short-day conditions (Laubinger and Hoecker, 2003).…”
Section: (Supplementarymentioning
confidence: 99%